The Legal Responsibility to the Family for Shackling People with Mental Illness During the Covid-19 Pandemic - Yuna Ariawan; Cempaka Dewi; Ratih Wulansari Manuaba; Chandranita Manuaba; Mokhamad Khoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2022)
During the COVID-19 pandemic until June 2020, there were 277,000 mental health cases in Indonesia. The number increase compared to 2019. The number of shackling due to mental illness increased from 5,200 in 2019 to 6,200 in 2020. Shackling is strictly prohibited because it violates the law and human rights. Criminal sanctions in Article 333 of the Criminal Code are prepared for those who shackle people with mental illness. The punishment stipulated in this article is also applied to people who intentionally give space to the deprivation of other people’s freedom.The program of “Indonesia Shackle-Free” was launched in 2010, the target was forced to be pushed back until 2019 and remains challenging to achieve. The number of shackling increases due to a lack of public understanding of mental health. This paper aims to explore further the relationship between the COVID-19 pandemic and the condition of people with mental illnesses (ODGJ) in Indonesia. Another impact of the COVID-19 pandemic on ODGJ is drug withdrawal because of the disruption of drug circulation during the pandemic. The allocation of health financing is also focused on dealing with the pandemic.Promotive efforts are expected to eliminate stigma, discrimination, and human rights violations for ODGJ in the community. Whereas, preventive efforts by developing parenting styles that support mental growth and development, communication, and education in the family are expected to provide appropriate mental health services for ODGJ when entering the rehabilitation stage